Konkurencyjność polskich gospodarstw specjalizujących się w produkcji mleka - Karolewska, Małgorzata (Competitiveness of Polish Farms Specializing in Milk Production, 2006)
The main case of the article is to estimate competitiveness of Polish farms specializing in milk production in comparison to selected countries in the world. The analysis is done on the basis of economy factors. 12 farms from the world have been analysed. Polish farms for the sake of low costs of milk production, relatively high price, and high income are competitive in comparison to the rest of the selected farms.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 374-378